Uma metodologia de referência para implantação da produção enxuta em operações hospitalares - Régis , Tatyana Karla Oliveira (2015)
The main objetive of this work is to develop a methodology for the implementation of lean manufacturing in hospital operations. For this purpose, it was initially performed an analysis of the relevant literature on the topics: lean manufacturing, hospital operations and lean services (focusing on health care services). Based on the literature, some categories of lean health were identified. The research is classified as qualitative, applied and exploratory, and was conducted through multiple case studies in three hospital operations in São Paulo state. Based on the literature and case studies, it was possible to suggest guidelines for the application of the lean techniques, organizing them in order to compose the proposed methodology for the implementation of the lean in hospital operations. First the methodology consisted of two phases: (I) initiatives to implement the lean; (II) the implementation of the lean techniques and the development of lean culture. After it was submitted to the experts' analysis on the subject (researchers, consultants and hospital management) with two goals: to be refined, or improved, based on the suggestions of the experts. The experts evaluated the methodology based on Platts’s (1993) criteria: feasibility, usability and utility. After the refinement and avaliation of the experts, the final proposal remained with the two phases, however, some suggestions were made and were considered to the upgrading of the methodology. The final methodology showed predominatly modifications in the second phase and considered the following aspects: the support of the senior management, the training of a team to manage the improvement projects, the empowerment of the improvement teams, the development of leaders in the lean technique, the binding of the implementation of the lean to the strategic planning, the performance of the improvement projects, as well as the management of all projects through the PDCA, a training program to the employees, the application of the kaizen events; the application of the Ishikawa diagram to identify the root cause of the losses and the development of appropriate performance indicators. The experts considered that the methodology: can be followed, can be easily followed and provide a useful step in the lean implementation on the operations health.